Tatbiq Namudaj Ad-Daur Al-La'bi Fi Tarqiyah Fahm Qawa'id An-Nahw wa As-Sharf Li Muhadatsah At-Tullab Fi Al-Madrasah Ats-Tsanawiyah Al-Ahliyah Swadaya Batang Serangan Langkat - Rahma, Ainur; S, Fahrurrozi (LPPM Universitas KH.A. Wahab Hasbullah, 2025)
This study aims to improve the understanding of nahwu and shorof (Arabic grammar and morphology) among eighth-grade students of MTs Swasta Swadaya Batang Serangan Langkat through the implementation of the role-playing learning model. The research used a classroom action research (CAR) approach based on the Kemmis and McTaggart model and was carried out in two cycles. Data collection instruments included pre-test and post-test, observation sheets, and open interviews. Quantitative data were analyzed using a paired t-test, while qualitative data were analyzed using the triangulation technique. The results showed a significant improvement in student achievement. In the first cycle, the average score increased from 54.60 to 71.70 (an increase of 31.32%), and in the second cycle from 69.70 to 83.67 (an increase of 20.04%). Observations and interviews also revealed that students became more confident, active, and accurate in applying Arabic grammatical rules in spoken communication. It can be concluded that the role-playing model is effective in improving students’ understanding of Arabic grammar and morphology in muhadatsah (Arabic conversation) and holds strong potential for application in broader language learning contexts. This study not only contributes practically to the context of Arabic language learning, but also reinforces the position of role-playing as a method that simultaneously addresses the linguistic and psychological aspects of learners. This is in line with Shaftel's theory regarding the importance of social-emotional experiences in meaningful learning processes.